(untitled) (Research, Society and Development, 2020)
Zinc (Zn) and iron (Fe) are the most deficient nutrients in the world population. Agronomic biofortification of Zn aims to increase concentration of the micronutrient in edible parts of staple crops without negatively affecting yield. However, the increase in grain Zn accumulation may affect grain Fe accumulation and bioavailability. In order to study these micronutrients in wheat grains, the objective of this study was to evaluate the concentrations of Zn and Fe in grains of wheat cultivars and to verify the effect of foliar Zn spraying to improve grain nutritional quality without negatively affecting yield. The field experiment was carried out in a randomized block design with four replicates, in a split-plot scheme, with plots being composed of five wheat cultivars widely cultivated in Southern Brazil (ORS 1403, ORS Vintecinco, BRS Gralha Azul, BRS Sabiá e TBIO Sintonia) and subplots composed of four Zn doses (0, 250, 500 e 1000 g ha-1) applied via foliar spraying at the maturation phenological stage. Grain yield varied between cultivars from 1328 to 4333 kg ha-1, but there was no significant effect of leaf Zn spraying. There was genotypic variation as to ability of the wheat cultivars to accumulate Zn in grains. The cultivars had different responses in grain Zn accumulation due to the foliar Zn spraying. There was an inverse relationship between Zn and Fe accumulation in the grains in four wheat cultivars.